A pilot study of optical neuronavigation‐guided brain biopsy in the horse using anatomic landmarks and fiducial arrays for patient registration. (29th May 2020) - Santistevan, Lawrence; Easley, Jeremiah; Ruple, Audrey; Monck, Sam; Randall, Elissa; Wininger, Fred; Packer, Rebecca A.
Abstract: Background: Optical neuronavigation‐guided intracranial surgery has become increasingly common in veterinary medicine, but its use has not yet been described in horses. Objectives: To determine the feasibility of optical neuronavigation‐guided intracranial biopsy procedures in the horse, compare the use of the standard fiducial array and anatomic landmarks for patient registration, and evaluate surgeon experience. Animals: Six equine cadaver heads. Methods: Computed tomography images of each specimen were acquired, with the fiducial array rigidly secured to the frontal bone. Six targets were selected in each specimen. Patient registration was performed separately for 3 targets using the fiducial array, and for 3 targets using anatomic landmarks. In lieu of biopsy, 1 mm diameter wire seeds were placed at each target. Postoperative images were coregistered with the planning scan to calculate Euclidian distance from the tip of the seed to the target. Results: No statistical difference between registration techniques was identified. The impact of surgeon experience was examined for each technique using a Mann‐Whitney U test. The experienced surgeon was significantly closer to the intended target (median = 2.52 mm) than were the novice surgeons (median = 6.55 mm) using the fiducial array ( P = .001). Although not statistically significant ( P = .31), for the experienced surgeon the median distance to target was similar when registering with the fiducial array (2.47 mm) and anatomic landmarks (2.58 mm). Conclusions and Clinical Importance: Registration using both fiducial arrays and anatomic landmarks for brain biopsy using optical neuronavigation in horses is feasible.